The Effect of Service Quality, Price Perception, and Brand Image on Feeling Value, and Customer Satisfaction at Dian Husada Mojokerto Hospital - Indarwati; Ida Bagus Cempena; Ida Bagus Udayana Putra (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
This study aims to determine the effect of service quality, perceived brand image price and perceived value on consumer satisfaction at Dian Husada Hospital, Mojokerto. The hypothesis in this study is that there is a partial effect of service quality on price perceptions on perceived value and service quality. And there is a significant effect of perceived service quality, price, brand image and perceived value simultaneously affect customer satisfaction at Dian Husada Hospital in Mojokerto. The population used in this study were 100 consumers at Dian Husada Hospital Mojokerto. The data analysis technique used is validity test, reliability test, classical assumption test, descriptive analysis, multiple linear regression analysis, multiple determination analysis, correlation coefficient analysis. The hypothesis test used is the F test and t test. Based on the t test results of Path Sub-Structure 1, service quality, price perception and brand image has a partial effect on perceived value. Based on the results of the t test Sub-Structure 2, the perceived service quality of price and value has a partial effect on service quality and brand image has no partial effect on customer satisfaction; Based on the results of the study of the F-Test Sub-Structure 1, the Sig. <0.05 is 0.000 <0.005, so the variables of Service Quality, Price Perception, and Brand Image have a significant influence on the Perceived Value. And based on the results of the study of the F-Test Sub-Structure Path 2, the value of Sig. <0.05 is 0.000 <0.005, so that the variables of Service Quality, Price Perception, Brand Image.